The economic experience: An introduction through experiments - Holt, Charles A.; Sprott, Erica R. (Princeton Princetion University Press, 2025)
This book presents a unique active-learning approach to economic thinking, providing a behavioral perspective on basic economic concepts ranging from trust to trade. Each chapter features a classroom experiment where students engage directly with the material as market participants, and chapters come with warm-up exercises, quizzes, and incisive summaries.